Strategi Marketing Mix dalam Menghadapi Persaingan Pasar : Studi Kasus Pada PT. Zamzam Sumbula Thoyyiba Tangerang Selatan - M Zein Ramadhan Rifa’I; Muhamad Zen (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2021)
Currently, the number of PIHKs in Indonesia in 2021 is 348 and the number of PPIUs to date is 1313, the large number has opened up increasingly fierce market competition. As time goes by, the interest of the Indonesian Muslim community who wants to perform the Hajj and Umrah is increasing. The purpose of this study was to the formulation and then the implementation and evaluation of the marketing mix strategy carried out by PT. Zamzam Sumbula Thoyyiba in the face of market competition, which consists of seven marketing mix variables developed, namely product, price, promotion, place, people, process and physical evidence. The research method used in this study is a qualitative research method that produces descriptive data expressed in the form of sentences and descriptions using data collection techniques, namely interviews, observations, documentation and other supporting data. The results of this study, the authors conclude that PT. Zamzam Sumbula Thoyyiba has formulated, implemented and evaluated the 7P marketing mix strategy in accordance with the company's goals and does not consider other companies to be competitors or enemies but friends of an association that can be invited to cooperate.